Image analysis method to quantify the effect of different treatments on the visual meat/shell ratio of half-shelled green lipped mussels (Perna canaliculus) - Kim, Min Geun; Alcicek, Zayde; Balaban, Murat O.; Atar, Hasan Huseyin (Wiley, 2014)
BACKGROUND Aquacultured green lipped mussel (Perna canaliculus) is the New Zealand export leader of seafood in terms of weight. Different treatments shrink mussel meat differently and affect the consumer perception of half-shelled mussels. In order to quantify this, digital images of half-shelled green lipped mussels subjected to two postharvest treatments (ultrahigh pressure (UHP) and heat treatment (HT)) and raw controls were taken. The ratio of the view area of the meat to that of the shell (labelled as 'visual condition index' (VCI)) was measured using image analysis. A polygonal region of interest was defined on the image to depict the boundary of the meat and to calculate the view area. RESULTS Raw mussels had a VCI of 85%. HT mussels had a much reduced VCI of 41%, indicating shrinkage of the meat due to heat. UHP treatment used as a shucking method resulted in a VCI of 83%. Since VCI is one measure of quality for the consumer, this quantitative method can be used in the optimization of shucking treatment (HT or UHP). CONCLUSION VCI can be used to optimize postharvest treatments to minimize meat shrinkage. This method can also be applied to other shellfish such as oysters and clams. (c) 2013 Society of Chemical Industry
Keywords: thermal treatment; image analysis; green lipped mussels; visual condition index; high pressure